Norwid according to Krasiński, or the disappointment of an unwelcome preceptor - Fiećko, Jerzy (Porównania, 2022)
The author presents the development of the relationship between Zygmunt Krasiński and Cyprian Norwid, with commenting and focusing on the former writer’s point of view, expressed in letters to a number of addressees. The author points to the reasons for Krasiński’s disappointment after his attempts to position himself as Norwid’s literary mentor and spiritual guide. Krasiński exerted pressure on his younger friend to change his style, accusing him of too much ambiguity and "darkness of words", which made it difficult to understand the ideas behind the poet's ambitious works. Norwid rejected this criticism and defended the right to individualise his style and language, assuming that literature must force the reader to make an individual effort and actively interpret a work of art. The author claims that the dispute revealed fundamental differences in the approach to the rules of creation: while Krasiński referred to the idea of a poet-bard and poet-guide, popular among the first generation of Romantics, Norwid went beyond the Romantic standard.